(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
A kind of regenerated Silk Fibroin (SF), nano-blended membrane, was made using an ionic liquid as a solvent. The membranes were characterized by SEM, XRD, FTIR, TG. The SEM showed that more agglomerations were observed with the increase of blended nano-TiO_2 (TD). XRD and FTIR verified that nano-TD made conformational changes in SF membrane and the conformation changes from random coil or Silk I into Silk II with the increase of nano TD. The TG analysis showed that pure silk fibroin membrane and nano TD membranes had only one apparent thermal transition region, at about 300 °C. Based on the mechanical performance test of SF membranes, tensile strength obviously increased when the amount of nano TD increased, which indicated that the mechanical strength improved with the addition of certain amount of nano TD.